2017
DOI: 10.3341/kjo.2016.0067
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Ocular Ischemic Syndrome and Risk Factors for Neovascular Glaucoma

Abstract: PurposeWe aimed to examine the clinical features and prognosis of ocular ischemic syndrome and to investigate the risk factors for the development of neovascular glaucoma (NVG).MethodsThe medical records from 25 patients (25 eyes) who were diagnosed with ocular ischemic syndrome were retrospectively analyzed. We recorded the length of time between symptom onset and diagnosis, visual acuity, intraocular pressure, clinical findings of the anterior and posterior segments of the eye, fluorescein angiography, syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
(32 reference statements)
1
27
0
4
Order By: Relevance
“…On the other hand, the risk of neovascular glaucoma attacks is high in patients with findings suggestive of anterior chamber neovascularization, such as rubeosis iridis and angle adhesion, those with marked stenosis (NASCET: ≥90%) of the cervical internal carotid artery ipsilateral to an ocular lesion, and those with an interval of ≥7 days after the appearance of ocular symptoms related to ocular ischemic syndrome. 8) In our patients, the interval from the appearance of decreased vision until neurosurgical intervention was 5 to 6 months. Furthermore, rubeosis iridis and angle occlusion were observed; therefore, it was necessary to consider a rapid revascularization-related increase in the ocular pressure in the chronic phase of advanced ocular ischemic syndrome.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…On the other hand, the risk of neovascular glaucoma attacks is high in patients with findings suggestive of anterior chamber neovascularization, such as rubeosis iridis and angle adhesion, those with marked stenosis (NASCET: ≥90%) of the cervical internal carotid artery ipsilateral to an ocular lesion, and those with an interval of ≥7 days after the appearance of ocular symptoms related to ocular ischemic syndrome. 8) In our patients, the interval from the appearance of decreased vision until neurosurgical intervention was 5 to 6 months. Furthermore, rubeosis iridis and angle occlusion were observed; therefore, it was necessary to consider a rapid revascularization-related increase in the ocular pressure in the chronic phase of advanced ocular ischemic syndrome.…”
Section: Discussionmentioning
confidence: 60%
“…Concerning the pathogenesis of neovascular glaucoma, chronic anterior ocular ischemia may induce functional or structural occlusion of the angle related to neovascularization around the iris, which is termed rubeosis iridis, and neovascular membrane, increasing the ocular pressure through aqueous humor outflow disorder. 2,3,8) Ocular ischemic syndrome is a condition in which ≥90% stenosis to complete occlusion of the carotid artery causes ischemic symptoms of the ipsilateral eye. [2][3][4][5][6][7] This syndrome is characterized by ocular pain and suddenly or gradually exacerbating low vision.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of anterior segment neovascularisation is believed to be a result of a stimulus from the posterior segment ischaemia. Posterior segment ischeamia usually arises from complications of ocular disorders, such as retinal venous and arterial occlusions, proliferative diabetic retinopathy, carotid artery obstructive disease and uveitis [4]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] As to OIS, NVG can occur in about 68% eyes and the risk increases with the length of time between symptom onset and diagnosis, as well as with the severity of ipsilateral carotid artery stenosis. [ 4 ] Having reviewed 301 cases of NVG in our department during the last 10 years, we found that there are >40 different kinds of diseases related to NVG, even local radiation therapy of nasopharyngeal carcinoma, which might compromise retinal circulation and induce retinal circulatory disturbance.…”
Section: Etiology and Prevalencementioning
confidence: 99%